Are there gender-specific differences in elementary motor speed ability? - Krug, J.; Voss, G.; Witt, M. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to analyse gender-specific differences in elementary motor speed ability. The reliability of 7 tests with 15 items was investigated using intra-class coefficients. Gender-specific differences of performance were analysed using independent samples t-tests. There were no differences between men and women in elementary motor speed. The structure of the elementary motor speed ability (reaction time, tapping, reactive speed and arbitrarily initiated speed) was investigated with confirmatory factor analysis. Here, we identified gender-specific differences in the structure using structural equation models. The models are characterized with a good model fit. Based on the present findings, conclusions for a gender-specific training of elementary motor speed abilities are derived.